ETHICAL COMPETENCY DAN STRATEGIC COMPETENCY TERHADAP PERTUMBUHAN BISNIS MAHASISWA - Yessy Natalia Halim (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2019)
In order to become an economic stimulator, or an entrepreneur, ability, knowledge, and skill are required. The purpose of this research is to understand the influence of entrepreneurial competencies such as ethical competency and strategic competency to the growth of business created by the university students. The population count for this research is 204 students, with 136 samples of International Business Management students from batch 2016, who are in Startup guild, and those whose business has been going on for more than 2 semesters. The data was collected using questionnaires distributed online as well as offline. The analysis tool used for this research was SPSS with regression analysis method. The result for this research are ethical competency does not influent business growth, while on the other hand, strategic competency influents business growth. Keywords: Ethical Competency, Strategic Competency, Business Growth